2016
DOI: 10.1080/21675511.2016.1241363
|View full text |Cite
|
Sign up to set email alerts
|

Pelger-Huët anomaly and Greenberg skeletal dysplasia: LBR-associated diseases of cholesterol metabolism

Abstract: Lamin B Receptor (LBR) is an inner nuclear membrane protein associated with the rare human diseases Pelger-Huët anomaly and Greenberg skeletal dysplasia. A new study has used CRISPR/Cas9-mediated genetic manipulations in a human cell system to determine that the molecular etiology of these previously poorly understood disorders is a defect in cholesterol synthesis due to loss of LBR-associated sterol C14 reductase activity. The study furthermore determined that disease-associated LBR point mutations reduce ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…A very recent study based on CRISPR-Cas9 technology showed that LBR point mutations are associated with a reduced sterol C14 reductase activity due and a lower affinity of LBR for NAPDH (Fig. 4a ) [ 36 ].…”
Section: Inner Nuclear Membrane (Inm) Proteins and Inherited Diseasesmentioning
confidence: 99%
“…A very recent study based on CRISPR-Cas9 technology showed that LBR point mutations are associated with a reduced sterol C14 reductase activity due and a lower affinity of LBR for NAPDH (Fig. 4a ) [ 36 ].…”
Section: Inner Nuclear Membrane (Inm) Proteins and Inherited Diseasesmentioning
confidence: 99%
“…Heterozygous LBR mutations lead to nuclear hyposegmentation of neutrophils without causing disease [ 6 , 59 , 87 ], while homozygous LBR mutations cause various malformations ranging from cardiac defects, brachydactyly and mental retardation (homozygous Pelger–Huët anomaly), severe skin disease (ichthyosis in mice) and prenatal death (Greenberg dysplasia) [ 6 , 87 ]. Mutations resulting in the Pelger–Huët anomaly are identified everywhere in the gene, while mutations causing Greenberg skeletal dysplasia are mainly found in the C -terminal region resulting in abnormality of the hydrophobic transmembrane domains [ 90 , 91 ]. Since mutations causing the Pelger–Huët anomaly result in bilobed neutrophil nuclei in heterozygotes and unsegmented, ovoid nuclei in homozygotes, the Pelger–Huët anomaly has been characterized mainly as a laminopathy [ 6 , 56 , 59 ].…”
Section: The Intricate Roles Of Lbr At the Nuclear Envelopementioning
confidence: 99%
“…Since mutations causing the Pelger–Huët anomaly result in bilobed neutrophil nuclei in heterozygotes and unsegmented, ovoid nuclei in homozygotes, the Pelger–Huët anomaly has been characterized mainly as a laminopathy [ 6 , 56 , 59 ]. On the contrary, as mutations associated with Greenberg skeletal dysplasia result in a deficiency of sterol reductase activity and in elevated levels of sterol intermediates, Greenberg dysplasia has been often characterized as a disease of cholesterol metabolism [ 12 , 87 , 89 , 91 ].…”
Section: The Intricate Roles Of Lbr At the Nuclear Envelopementioning
confidence: 99%
See 1 more Smart Citation
“…3 It has been reported that the lamin B receptor (LBR) mutations are the cause of PHA in humans. 13 The lamin B receptor is an evolutionary conserved, multifunctional protein. 14 LBR is an inner nuclear membrane protein that anchors the lamina and the heterochromatin to the inner nuclear membrane and has been shown to be significant for the normal morphologic maturation of granulocytes.…”
Section: Introductionmentioning
confidence: 99%